Aplikasi Pencacah Pakan Ternak pada Peternak Kambing Isbani Farm - Warji Warji; Tamrin Tamrin (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2022)
The feed given to goats is generally in the form of grass and cocoa pods. The grass that is given directly without being chopped is not eaten as a whole by the goat, but what is chopped first is eaten until it runs out. This service program aims to apply a forage chopper machine for goats at Isbani Farm so that the forage becomes fine in size. The method for reducing or smoothing the size of forage is to use a chopper in the chopping process. This chopper is in the form of two blades mounted on the axle and driven by diesel so that it can rotate and chop forage material. Service activities include problem formulation with partners, preparation of chopper machines, training on the use of chopping machines for partners and program evaluation. Partners are very open in conveying problems and very cooperative in coordinating. The animal feed material chopper machine can be well prepared; covering frame; the chopper and the driving motor. The training and application of the counting machine to partners went well; partners can absorb the knowledge and skills provided by the community service team. Evaluation of the service program went well; partners' knowledge increased by about 45%. It is necessary to conduct training in making silage or durable feed from agricultural waste feed ingredients such as corn stalks, rice straw and cassava leaves. It is necessary to create a sustainable program so that the partner assistance process is sustainable.